(untitled) (Bangladesh Journal of Agricultural Research, 2017)
A study was carried out in Kahramanmaras region of Turkey during 2012-13 having ten subregions namely, Afsin, And?r?n, Caglayancerit, Ekinozu, Elbistan, Göksun, Center, Nurhak, Pazarc?k and Türkoglu to determine the range, density and frequency of weeds in apple orchards. In the orchards 133 weed species from 31 families were determined. The average density of weeds was 112.49 plants m-2. The maximum density of weed species was found in Göksun (127.30 plants m-2) followed by Elbistan (126.13 plants m-2), Ekinozu (125.95 plants m- 2), Afsin (120.39 plants m-2), Center (117.94 plants m-2) and Caglayancerit (114.90 plants m-2), and the minimurn density was determined in Pazarc?k (69.51 plants m-2). From the identified 133 weed species one species belonged to Pterydophyta, 2l species to Monocotyledoneae and 111 species to Dicotyledoneae. The average densities of the weed species over l0 subregions for Agropyron repens (L.) P. Beauv., Chenopodium album L., Bromus arvensis L. and Amaranthus retroflexus L. were found to be 13.76, 12.17, 12.10 and 10.76 plants m-2, respectively. With regard to frequency of occurrence, C. album L. was detected more than 56% in six subregions excluding And?r?n, Pazarc?k, Türkoglu and Center; A. retroflexus L. more than 54% in 7 subregions excluding Center, Pazarc?k and Türkoglu and A. repens (L.) P. Beauv. more than 50% in 10 subregions. Frequency of occurance of Cynodon dactylon (L.) Pers. was observed 50.1, 50.9, 76.9% in Afsin, Caglayancerit and And?r?n, respectively and it was below 50% in other 7 subregions. In terms of coverage, Alopecurus myosuroides Huds., A. retroflexus, A. repens, B. arvensis, C. album, Convolvulus arvensis L., C. dactylon and Lactuca serriola L. were determined to be within the range of 20.2 to 48.2% in the study areas while the other species were below 20%. Bangladesh J. Agril. Res. 42(1): 87-102, March 2017